(untitled) (The Pakistan Development Review, 2010)
Government cannot roll over the debt forever (ponzi game is not allowed). In the long run, inter-temporal budget constraint has to be satisfied, which is possible either through government spending adjustment or increasing government revenues. So current budget deficit calls for adjustment, in the future, in spending or revenues. There are four hypotheses, in the literature, in this regard: the tax-and-spending hypothesis, the spending-and-tax hypothesis, bi-directional causality between government revenues and government expenditures, and independence of taxes and expenditures hypothesis. The last hypothesis, however, have negative implications, in the long run, in terms of debt sustainability and inflation